Grain-size parameters and diatom records as indicators of environmental changes along the southern Brazilian coastal plain - Cristiane Bahi dos Santos; Iran Stallivière Corrêa; Jair Weschenfelder; Jeffery Robert Stone (International Journal of Sediment Research)
Connections between changes in sediment distribution and diatom species are sensitive to environment-related deposition patterns of fine-grained sediment. A large lagoon in the southernmost Brazilian coastal plain was selected to test the sensitivity of diatoms to sediment changes and their ability to classify depositional environments. Selected grain-size parameters, including mean grain size, skewness, kurtosis, standard deviation, and sand-silt-clay ratios, were evaluated for interpretation. The trigonal diagram shows that most of the lagoon sub-bottom deposits lie in the fine-grained tail. Silt is dominant within the Holocene fluvial-estuarine, estuarine-transitional, and shallow marine deposits. Sand fractions (> 76%) are distributed in the coastal barrier and in a few fluvial-estuarine intervals. Most deposits are polymodal, lying between poorly sorted sediment, indicating a low-energy depositional environment. The results were interpreted as indicated by the Principal Component Analysis (PCA), which revealed resulting shifts in sediment and diatom composition connected to five sedimentary facies controlled by sea-level oscillations. Diatom species recovered from sediment cores have distinctive capacities for living under high marine, freshwater, and terrestrial conditions. Each quadrant of the PCA reflects the adaptation of species to particular depositional conditions during the Late Pleistocene and Holocene. Allochthonous taxa provide valuable ecological information about adjacent environments in the coastal area, offering insight into the paleogeography of the study area. The major advantage of the analytical methods is their applicability in distinguishing different environments involving mixed deposition and transport mechanisms. The sediment deposited on the bottom of a large lagoon provide significant implications not only for sedimentological analysis by improving understanding of high deposition of mud and fine-grained sands but also for predictions of the source-to-sink routes.